Dysregulation of hypoxia-inducible factor by presenilin/γ-secretase loss-of-function mutations - Kaufmann, Muriel R.; Barth, Sandra; Konietzko, Uwe; Wu, Bei; Egger, Sascha; Kunze, Reiner; Marti, Hugo; Hick, Meike; Müller, Ulrike C.; Camenisch, Gieri; Wenger, Roland H. (The journal of neuroscience, 2013)
Presenilin (PSEN) 1 and 2 are the catalytic components of the γ-secretase complex, which cleaves a variety of proteins, including the amyloid precursor protein (APP). Proteolysis of APP leads to the formation of the APP intracellular domain (AICD) and amyloid β that is crucially involved in the pathogenesis of Alzheimer's disease. Prolyl-4-hydroxylase-domain (PHD) proteins regulate the hypoxia-inducible factors (HIFs), the master regulators of the hypoxic response. We previously identified the FK506 binding protein 38 (FKBP38) as a negative regulator of PHD2. Genetic ablation of PSEN1/2 has been shown to increase FKBP38 protein levels. Therefore, we investigated the role of PSEN1/2 in the oxygen sensing pathway using a variety of genetically modified cell and mouse lines. Increased FKBP38 protein levels and decreased PHD2 protein levels were found in PSEN1/2-deficient mouse embryonic fibroblasts and in the cortex of forebrain-specific PSEN1/2 conditional double knock-out mice. Hypoxic HIF-1α protein accumulation and transcriptional activity were decreased, despite reduced PHD2 protein levels. Proteolytic γ-secretase function of PSEN1/2 was needed for proper HIF activation. Intriguingly, PSEN1/2 mutations identified in Alzheimer patients differentially affected the hypoxic response, involving the generation of AICD. Together, our results suggest a direct role for PSEN in the regulation of the oxygen sensing pathway via the APP/AICD cleavage cascade.